Diagnosis and management of hepatic encephalopathy: The French recommendations. (24th January 2023) - Thabut, Dominique; Bouzbib, Charlotte; Meunier, Lucy; Haas, Manon; Weiss, Nicolas; Louvet, Alexandre; Imbert‐Bismut, Francois; Mochel, Fanny; Nadjar, Yann; Santiago, Antoine; Thevenot, Thierry; Duhalde, Véronique; et al.
Abstract: Hepatic encephalopathy (HE) is a frequent and severe complication of liver disease with poor patient outcomes. However, it is a poorly understood complication, with no consensus for diagnosis. Therefore, HE is often underdiagnosed. Differential diagnosis may be cumbersome because of non‐specific symptoms, such as confusion, cognitive disorders, the aetiological factors of cirrhosis and comorbidities, which are often observed in cirrhotic patients. Therefore, an overt or covert form of HE should be systematically investigated. Advice is provided to drive patient work‐up. Effective treatments are available to prevent or treat HE bouts, but the issue of single or combination therapy has not been resolved. Transjugular intrahepatic portosystemic shunt (TIPS) placement largely improved the prognosis of cirrhotic patients, but HE occurrence of HE is often a fear, even when post‐TIPS HE can be avoided by a careful selection of patients and preventive treatment. HE is an indication of liver transplantation. However, its reversibility post‐transplantation and the consequences of transplantation in patients with other causes of neurological disorders remain controversial, which supports the performance of an extensive work‐up in expert centres for this subset of patients. The present guidelines assist clinicians in the diagnosis of the overt or covert form of HE to implement curative and preventive treatments and clarify which patients require referral to expert centres for consideration for liver transplantation. These guidelines are very clinically oriented and address different frequent clinical issues to help physicians make bedside decisions.